Kewajiban dan hak negara dan warga negara indonesia - Cairina, Launa Ervi; Yuwafi, Khamda; wulandari, selvia ayu (Maliki Interdisciplinary Journal, 2025)
The reciprocal relationship between the state and citizens is the main foundation of a democratic state system. This article comprehensively discusses the rights and obligations of the state and Indonesian citizens as stipulated in the 1945 Constitution, as well as how they are implemented in the life of the nation and state. The focus of the discussion includes the definition of citizens, the rights and obligations of citizens according to experts, the principle of balance of rights and obligations in Pancasila, as well as the rights and obligations of the state which include government management, natural resources, and legal protection. In addition, this article reviews the role of the legal system and law enforcement agencies in ensuring the protection and enforcement of rights and obligations, as well as the importance of active community participation in overseeing the running of the government. The article also emphasizes that collective awareness of rights and obligations is key to the creation of social justice, national stability and good governance. It is hoped that this article can serve as a reflective and practical basis for building a more just, prosperous and democratic order of state life.